2014
DOI: 10.1002/elan.201300426
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Attributes of Electrochemistry in Tandem with Electrospray Mass Spectrometry

Abstract: Electrolytic efficiency of battery‐operated flow‐through thin‐layer electrochemical (EC; echem) cell used in EC/ESI‐MS was investigated. Two stainless steel capillaries joined by PTFE tubing formed the thin‐layer EC cell. Echem reaction efficiency of ferrocyanide, dopamine and hydroquinone oxidation in the EC cell was low and decreased with increasing MeOH volume fraction in the MeOH/H2O carrier solutions with low conductivity. Water oxidation dominated the cell current and migration of ferrocyanide was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
(126 reference statements)
0
10
0
Order By: Relevance
“…It is well known that an ESI source can be considered as an electrolytic cell where redox reactions may occur via electrolysis . Previous studies suggested that electrochemical oxidation reactions occurred only in a positive ESI source and electrochemical reduction reactions took place only in a negative ESI source . In this study, however, oxidization reactions were observed not only with positive ESI‐MS, but also with negative ESI‐MS without significant difference in the extent of reactions (Fig.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…It is well known that an ESI source can be considered as an electrolytic cell where redox reactions may occur via electrolysis . Previous studies suggested that electrochemical oxidation reactions occurred only in a positive ESI source and electrochemical reduction reactions took place only in a negative ESI source . In this study, however, oxidization reactions were observed not only with positive ESI‐MS, but also with negative ESI‐MS without significant difference in the extent of reactions (Fig.…”
Section: Resultsmentioning
confidence: 48%
“…Previous studies have reported such redox reactions occurring in an ESI source . It is easy to understand that compounds with relatively low redox potential can be oxidized in a positive ESI source and those with relatively high redox potential could be reduced in a negative ESI source . Redox reactions taking place in the ESI source have been well studied in terms of mechanisms, theories, and applications .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidation of sample constituents at the ES emitter to which the high (kV) positive voltage is applied, which changes sample composition, has been documented in positive ion mode ESI MS. ,,, Oxidations occur during the ESI in the strong electric field at the ES emitter. For example, during ESI of DA, under standard ESI MS conditions, DA has been shown to oxidize to DA quinone [DAQ + H] + m / z 152 as the OP (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…At higher pH ∼6, ion signal of [CA+H] + is lower than at pH 3, as shown in Fig 3a (absolute intensity of the base peak is 2000 counts). Both the higher pH 6 and the lower conductivity of this solution can suppress the ionization efficiency 44. At the higher pH proton‐bound and sodium‐bound dimers of CA, [2CA+H] + (m/z 389) and [2CA+Na] + (m/z 411) (Fig.…”
Section: Resultsmentioning
confidence: 99%